Correction to: Exploring the Relationship Between Lasting, Quality Social Bonds and Intermittency in Offending - Metcalfe, Christi (American journal of criminal justice, 2019)
The original version of this article, unfortunately, was missing a decimal point in Table 2. The effect size (b) for Proportion of Time on the Street in Waves 1–6 should be −2.403 instead of −2403.